2015
DOI: 10.1016/j.idairyj.2015.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of galactooligosaccharides using sweet and acid whey as a substrate

Abstract: a b s t r a c tTwo commercial available lactases from Aspergillus oryzae and Kluyveromyces lactis were used to study the synthesis of galactooligosaccharides (GOS) in sweet and acid whey. At 38 g L À1 initial lactose concentration, the A. oryzae enzyme gave a GOS yield of 10.91 ± 0.01% in lactose solution, 10.93 ± 0.18% in sweet whey and 11.32 ± 0.59% in acid whey. Thus, the components in whey did not influence the enzymes transgalactolytic activity. On the other hand, the K. lactis enzyme showed a strong depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 25 publications
(24 reference statements)
8
45
0
Order By: Relevance
“…a). The obtained results proved to be comparable with ones previously reported for the sweet whey in the literature in terms of achieved yields (40–67 g L −1 ) (Song et al ., ; Fischer & Kleinschmidt, ; Mueller et al ., ), and also are in accordance with typical yields for pure lactose conversion (not exceeding 30% w/w) for β ‐ galactosidase from A. oryzae . The higher yields were only accomplished with more concentrated whey solutions (with corresponding 40% w/v lactose concentration) using β ‐ galactosidase from Kluyveromyces lactis (Lactozym ® 3000L) (Lisboa et al ., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…a). The obtained results proved to be comparable with ones previously reported for the sweet whey in the literature in terms of achieved yields (40–67 g L −1 ) (Song et al ., ; Fischer & Kleinschmidt, ; Mueller et al ., ), and also are in accordance with typical yields for pure lactose conversion (not exceeding 30% w/w) for β ‐ galactosidase from A. oryzae . The higher yields were only accomplished with more concentrated whey solutions (with corresponding 40% w/v lactose concentration) using β ‐ galactosidase from Kluyveromyces lactis (Lactozym ® 3000L) (Lisboa et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, it can be seen that obtained results (total GOS concentrations) using both substrates are quite similar (Fig. ) at all examined concentrations, indicating that the whey complex composition was not hampering lactose accessibility towards enzyme, and more importantly, did not impose presumed enzyme inactivation mostly expected by high concentrations of different minerals (Torres et al ., ; Fischer & Kleinschmidt, ). Thus it can be concluded that sweet whey powder could be used as a reasonable substitution of lactose.…”
Section: Resultsmentioning
confidence: 99%
“…It reduces water activity and shifts the enzyme activity from hydrolytic towards synthesis of oligosaccharides [Matsue & Miyawaki, 2000]. Sodium salt (NaCl) was used for the tests since sodium ions are mentioned as β-galactosidase activators [Fischer & Kleinschmidt, 2015;Zhang et al, 2013]. The use of salt at the concentration of 0.05 mol/L, 0.1 mol/L and 0.25 mol/L increased the maximum content of gal-mannitol (in the total sugar) by 7.1%, 8.7% and 12.8% respectively (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies on GOS production from whey have been conducted on (protein‐containing) rehydrated powder of whey (Fischer & Kleinschmidt, ; Jovanovic‐Malinovska, Fernandes, Winkelhausen, & Fonseca, ; Klein et al, ; Lisboa et al, ; T. S. Song et al, ) and on (protein‐free) rehydrated powder of whey UF‐permeate (Foda & Lopez‐Leiva, ; López Leiva & Guzman, ; Rustom, Foda, & López‐Leiva, ; Pocedičová, Čurda, Mišún, Dryáková, & Diblíková, ) using various processing technologies including stirred tank reactors (STR), packed bed reactors, and inert and catalytic membrane reactors. These studies have used either fungal [derived from Aspergillus sp .…”
Section: Introductionmentioning
confidence: 99%
“…(Fischer & Kleinschmidt, ; Jovanovic‐Malinovska et al, ; López Leiva & Guzman, ; Rustom et al, ) and Kluyveromyces lactis (Fischer & Kleinschmidt, ; Foda & Lopez‐Leiva, ; Klein et al, ; Lisboa et al, ; Pocedičová et al, ; Rustom et al, )] or bacteria‐originated (derived from Lactobacillus paracasei [T. S. Song et al, ]) enzymes. It has been shown by several authors (Fischer & Kleinschmidt, ; Pocedičová et al, ; Splechtna et al, ) that the type of substrate matrix (i.e., whether it is a buffered lactose, buffered lactose with addition of salts, whey, UF‐permeate, etc.) may affect both lactose conversion and GOS yield of β‐galactosidases of various sources.…”
Section: Introductionmentioning
confidence: 99%